Pembelajaran Berkarakteristik Inovatif Abad 21 Pada Materi Thaharah dengan Model Pembelajaran Problem Based Learning (PBL) - Dhillan Azaly Alfarozy (Cakrawala: Jurnal Pendidikan, 2022)
The process of developing the Learning Implementation Plan (RPP) should be adjusted to several guidelines that have been regulated in the current regulation of the minister of education regarding the 2013 Curriculum. This study aims to find out the results of the analysis of the Learning Implementation Plan (RPP) document for PAI lesson content for Thaharah at the IT Daar Al-Faradis Middle School based on the Adiwerna Islamic Boarding School in the 2021/2022 academic year. This study uses data sources as many as 3 RPP PAI with a focus on analysis of the learning model used. The research method used in this research is descriptive qualitative. The instrument used was the researcher himself, the component completeness table, the systematic preparation of the RPP components and guidelines for reviewing the RPP. The results showed that the three lesson plans were analyzed using different learning models. The three learning models used in the preparation of the lesson plans include the PBL model, Discovery Learning and Inquiry Learning. The three learning models are included in the 21st century innovative learning model. However, there are several components in the RPP that are not in accordance with the guidelines for preparing the RPP contained in Permendikbud number 22 of 2016